First two cockroaches from the early Eocene of western Rajasthan, India (Insecta: Blattodea) - Patel, Raman; Rana, Rajendra Singh; Nel, Andre (Zootaxa, 2021)
We describe the first two Blattodea from the early Eocene Palana Formation of the Gurha opencast lignite mine, western Rajasthan, India. Although it is not possible to attribute them to a precise family, these large wings suggest a warm and humid paleoclimate for the area at that time.